Leading with Emotional Intelligence. - Stein, Steven J. (John Wiley & Sons, Incorporated, 2017)
A roadmap to success for tomorrow's leaders The EQ Leader provides an evidence-based model for exceptional leadership, and a four-pillar roadmap for real-world practice. Data collected from thousands of the world's best leaders--and their subordinates--reveals the keys to success: authenticity, coaching, insight, and innovation. By incorporating these methods into their everyday workflow, these leaders have propelled their teams to heights great enough to highlight the divide between successful and not-so-successful leadership. This book shows you how to put these key factors to work in your own practice, with clear examples and concrete steps for improving skills and competencies. New data from the author's own research into executive functioning describes the neurological aspects of leadership, and a deep look at the leaders of tomorrow delves into the fundamental differences that set them apart--and fuel their achievement. Leadership is changing, both in look and practice; strictly authoritative approaches are quickly losing ground as today's workers discover the power of collaboration and the importance of interpersonal awareness. This book provides step-by-step guidance for leading from within this space, with evidence-based approaches for success. Lead authentically to inspire and motivate others Support employee's needs and nurture development Communicate with purpose, meaning, and vision Foster ingenuity, imagination, and autonomous thinking An organization's success rests on the backs of its leadership. At all levels, true leadership is about much more than management and task distribution--it's about commitment, collaboration, nurturing talent, developing skills, fostering relationships, and so much more. The EQ Leader integrates the essential factors of successful leadership into a concrete blueprint for the future's leaders.